What Happens After a Positive Primary Care Autism Screen Among Historically Underserved Families? Predictors of Evaluation and Autism Diagnosis. Issue 7 (September 2021) - Kuhn, Jocelyn; Levinson, Julia; Udhnani, Manisha D.; Wallis, Kate; Hickey, Emily; Bennett, Amanda; Fenick, Ada M.; Feinberg, Emily; Broder-Fingert, Sarabeth
ABSTRACT: Objective: Families, pediatric providers, and service systems would benefit from expanded knowledge regarding (1) who is most likely to receive a recommended diagnostic evaluation after a positive primary care–administered autism screen and (2) of those who screen positive, who is most likely to be diagnosed with autism? Method: Participants included 309 predominantly low-income, racial/ethnic minority parents and their child, aged 15 to 27 months, who screened positive on the Modified Checklist for Autism in Toddlers, Revised with Follow-Up (M-CHAT-R/F). Generalized estimating equations were used to fit models of predictors for each binary outcome: receiving a diagnostic evaluation and receiving an autism diagnosis on evaluation. Results: Significant predictors of diagnostic evaluation receipt included the parent being older or non-Hispanic and the child having private insurance, lower child communication functioning, or receiving Early Intervention services. Significant predictors of an autism diagnosis on evaluation included male child, lower child communication functioning, screening directly in the parent's preferred language, White/non-Hispanic parent, and no parent history of mood disorder. Conclusion: Children with younger parents, Hispanic ethnicity, relatively higher communication skills, public insurance, and no Early Intervention services were less likely to receive recommended diagnostic care. Reduced likelihood of autism diagnosis after a positive screen in non-White/non-Hispanic subgroups supports previous research indicating issues with M-CHAT-R/F positive predictive power for racial/ethnic minorities. The use of telephonic interpreters to administer screens, as opposed to directly screening in families' preferred languages, may lead to identification of fewer true autism cases. Thus, multilingual clinical staff capacity may improve positive predictive power of autism screening.